SOSIALISASI MEKANISME PENETAPAN AHLI WARIS SECARA ISLAM DI KECAMATAN PADALARANG KABUPATEN BANDUNG BARAT - Wahyudi Wahyudi (ABISATYA DINAMIKA ISWARA PUBLISHING, 2025)
The public's understanding of Islamic inheritance law is still low and often causes conflicts in the distribution of inheritance. To overcome these problems, the socialization of the mechanism for determining heirs in Islam is carried out which aims to increase public knowledge and awareness of the importance of implementing sharia inheritance law. This activity was carried out by a service team from the Indonesian Computer University involving one resource person from the Law Study Program. The implementation method includes lectures, group discussions, case studies, and evaluation using pre-test and post-test questionnaires. The results of the evaluation showed an increase in participants' understanding, with an average pre-test score of 4.5 to 8.3 in the post-test. The enthusiasm of the participants was very high and many expected regular follow-up programs. This activity has a positive impact in helping the community understand the mechanism for determining heirs and resolve disputes peacefully in accordance with sharia.